SIPKUMHAM and The Rise of Digitalization in the Ministry of Law and Human Rights - Nur Rahmawati Waji (Badan Strategi Kebijakan Hukum, 2022)
The use of digital has accelerated after Covid-19 Pandemic which now has turned to the third year. The implementation of digital development is the emergence of digital system in government administrations which is known as Electronic Government. The situation encourages the use of digital government, or more specifically the use of digital system in government administration system or known as E-Government. Digitalization occurs in many areas including in law and human rights. However, the impact of digital acceleration on working procedures at the Ministry of Law and Human Rights becomes the main focus, currently. This article aims to unfold the process of digital acceleration procedures at the Ministry of Law and Human Rights, handling law and human rights affairs. In particular this article will discuss the SIPKUMHAM application. In fact, the attachment of digitalization, has been stated by Law and Human Rights Research and Development Agency within the SIPKUMHAM which contains databases regarding to the issues and its control. This study uses empirical juridical research of qualitative approach. We found that databases are needed to make evidence-based policy. The SIPKUMHAM application becomes a research information system that is able to provide factual data in terms of policy recommendations and tangible forms of performance to the Republic of Indonesia.